Formulation and Evaluation of Ibuprofen Gel using a Natural Polymer (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Prolonged oral use of ibuprofen for chronic conditions such as arthritis may cause peptic ulcer disease. Topical gel formulations have been developed to overcome this shortcoming. An immediate release formulation of ibuprofen would find application as a transdermal patch for management of chronic inflammatory conditions. In our study, a topical ibuprofen gel was found to have a better release profile for the active pharmaceutical ingredient than the marketed brand.
Keywords: Ibuprofen; gel; immediate release; peptic ulcer disease